2014
DOI: 10.1158/1078-0432.ccr-14-1293
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 1,115 Patients Tested for MET Amplification and Therapy Response in the MD Anderson Phase I Clinic

Abstract: Purpose: This study aimed to assess MET amplification among different cancers, association with clinical factors and genetic aberrations and targeted therapy response modifications.Experimental Design: From May 2010 to November 2012, samples from patients with advanced tumors referred to the MD Anderson Phase I Clinic were analyzed for MET gene amplification by FISH. Patient demographic, histologic characteristics, molecular characteristics, and outcomes in phase I protocols were compared per MET amplification… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
6
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(88 citation statements)
references
References 42 publications
5
75
6
2
Order By: Relevance
“…The proportion of BRAF -mutant colorectal tumor samples coharboring MET molecular alterations is unknown, but a large series of 1,115 samples from any tumor types has previously reported that MET amplifi cation was associated with a higher prevalence of BRAF mutations compared with nonamplifi ed tumors ( 22 ). In our collection of 17 additional BRAF -mutant colorectal cancer samples from chemonaïve patients, we were able to fi nd MET -amplifi ed subclones in three cases.…”
Section: Discussionmentioning
confidence: 76%
“…The proportion of BRAF -mutant colorectal tumor samples coharboring MET molecular alterations is unknown, but a large series of 1,115 samples from any tumor types has previously reported that MET amplifi cation was associated with a higher prevalence of BRAF mutations compared with nonamplifi ed tumors ( 22 ). In our collection of 17 additional BRAF -mutant colorectal cancer samples from chemonaïve patients, we were able to fi nd MET -amplifi ed subclones in three cases.…”
Section: Discussionmentioning
confidence: 76%
“…As yet, there is no clinically validated method for defining cMET amplification, and thus the actual rate of amplification in tumour samples varies significantly between studies. The correlation between sensitivity to cMET-inhibitory agents and cMET amplification remains unclear, with various studies reporting correlation [48][49][50][51], transient sensitivity [52], or no correlation [53][54][55], and as such it will be important to define a method by which copy number can be accurately determined and clinically validated. In high grade serous ovarian cancer, the TCGA cBioPortal [56,57] reveals mutations in the Met gene to be present in 1.3% of cases, and amplifications in 1.6%.…”
Section: Mis-regulation Mechanisms Of Hgf/cmetmentioning
confidence: 99%
“…Interestingly, a number of phase I trials of HGF/cMET targeting agents have included patients with ovarian cancer, [82,97,88,54,98,61] …”
Section: Hgf/cmet Inhibitors Trials In Ovarian Cancermentioning
confidence: 99%
“…Under normal circumstances HGF activation of Met is tightly controlled by mechanisms such as paracrine ligand delivery and ligand activated receptor internalization and degradation. Despite these controls, the HGF/Met signaling contributes to oncogenesis and tumor progression in several human cancers, including gastroesophageal, colorectal, lung, breast, renal and more (1,2).…”
Section: Introductionmentioning
confidence: 99%